On-line tourism destination marketing: Case study of Canadian Atlantic provinces - Roselyne , N. Okech (2013)
Tourism destinations are faced with increased and intense competition in marketing and would use all means to promote and attract tourists to their sites. The tourists’ desire for pleasing experiences should compel tourist businesses to consider effective means of destination marketing.Many tourists are turning to the internet as a source for travel and tourism information from attractions to visit to accommodation to patronize. Advertising, brochures, web pages are among various ways of promoting the destination however potential travelers are relying on destination reviews by other travelers who have visited the destination. The measurement of this factor is often overlooked but is an essential factor in marketing strategies to effectively respond to positive or negative experiences of the destination image. Hence in order for them to succeed, they must have a sound online marketing and promote themselves in a unique way all in the effort of attracting tourists. This study investigates the extent to which four provinces in Atlantic Canada, namely, Newfoundland, Prince Edward Island, New Brunswick, and Nova Scotia are marketing themselves on the internet to attract both domestic and international tourists and thus reaching out to the global market. The paper using a case study approach, identifies the factors in successful destination marketing and also explores the role and impact of traveler reviews to the four destinations using trip advisor as a virtual community and one of the most popular and reliable source of reviews.